2020
DOI: 10.3389/fbioe.2020.576969
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Modified Titanium Implant Materials: A Way Toward Improved Antibacterial Properties

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 396 publications
(348 reference statements)
0
63
0
1
Order By: Relevance
“…Compared with nanoparticles of other metals such as Ag, Cu, and Zn, Au nanoparticles have higher biological safety and relatively weak antibacterial ability. Possible mechanisms include direct contact with the outer membrane of bacteria causing membrane disruption, the production of ROS, photothermal effects, and photocatalysis (Liu et al, 2020). Among them, the membrane damage caused by direct contact plays a major role (Liu et al, 2020).…”
Section: Aumentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with nanoparticles of other metals such as Ag, Cu, and Zn, Au nanoparticles have higher biological safety and relatively weak antibacterial ability. Possible mechanisms include direct contact with the outer membrane of bacteria causing membrane disruption, the production of ROS, photothermal effects, and photocatalysis (Liu et al, 2020). Among them, the membrane damage caused by direct contact plays a major role (Liu et al, 2020).…”
Section: Aumentioning
confidence: 99%
“…Possible mechanisms include direct contact with the outer membrane of bacteria causing membrane disruption, the production of ROS, photothermal effects, and photocatalysis (Liu et al, 2020). Among them, the membrane damage caused by direct contact plays a major role (Liu et al, 2020). Au is mainly used as a coating in tooth restoration, and there is no report on the application of Au alloys in orthopedics.…”
Section: Aumentioning
confidence: 99%
“…Among them, the localized release of antibiotics, organic or inorganic antibacterial agents, such as metal ions or nanoparticles, can be cited [9][10][11][12]. Finally, topographical modifications should be synergistically designed to be suitable for both the optimization of tissue integration and infection passive prevention, such as through surface nanotextures [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial infection is one of the major concerns in tissue regeneration and wound healing, and inhibition of bacteria growth plays a key role in the wound healing process. [ 21 ] In addition to the application of antibiotics, different antibacterial approaches have been investigated including metal ions, [ 22 ] nanoeffect, [ 23 ] nitric oxide, [ 24 ] photocatalysis [ 25 ] and photothermal treatment. [ 21a ] Previous studied have shown that both photothermal and photocatalytic effect are able to inhibit bacteria growth.…”
Section: Discussionmentioning
confidence: 99%